A convenient route to mono-trans polyunsaturated free fatty acids. Issue 2 (April 2022) - Vetica, Fabrizio; Sansone, Anna; Ferreri, Carla; Chatgilialoglu, Chryssostomos
Trans unsaturated fatty acids in humans may be originated both from dietary supplementation and from an endogenous free-radical-catalyzed cis−trans isomerization of fatty acid residues in naturally occurring cis lipids. The latter process affords geometrical isomers and the polyunsaturated fatty acid mono-trans isomers were demonstrated to be connected with stress conditions in living organisms. Synthesis of mono-trans polyunsaturated fatty acid is useful for analytical and biological research, and in this case, the availability of free fatty acids is needed as well as the possibility of mg scale of the synthetic protocol. Herein, we report a simple synthetic route to mono-trans isomers of arachidonic acid, eicosapentaenoic acid, and docosahexaenoic acid, which includes thiyl radical-catalyzed isomerization reaction of polyunsaturated fatty acid methyl esters and fraction isolation of mono-trans mixture isomers followed by optimization of hydrolysis condition to free fatty acids and purification of each mono-trans polyunsaturated fatty acid. Our approach to mono-trans polyunsaturated fatty acids as free acids can reach the mg scale, thus fostering more applications to biochemical and biological studies.